Food Fights: Cookbook Rhetorics, Monolithic Constructions of Womanhood, and Field Narratives in Technical Communication. Issue 1 (2nd January 2016) - Moeller, Marie E.; Frost, Erin A.
ABSTRACT: Field narratives that (re)classify technical genres as liberating for women risk supporting the notion that feminism is a completed project in technical communication scholarship. This article suggests that technical communicators reexamine the impact of past approaches to critical engagement at the intersections of gender studies and technical communication; cookbooks provide a material example. The authors illustrate how a feminist approach to cookbooks as technical/cultural artifacts can productively revise field narratives in technical communication.